Escherichia coli lipopolysaccharide affects intestinal mucin secretion in weaned pigs - Zapata, Deny J; Rodríguez, Berardo de J; Ramírez, María C; López H, Albeiro; Parra S, Jaime (Revista Colombiana de Ciencias Pecuarias, 2015)
Background: to the best of our knowledge, the effects of lipopolysaccharide (LPS) from Escherichia coli on goblet cells and intestinal mucin secretion of weaned pigs has not been reported, and it is unknown whether these effects could trigger enteritis. Objective: to determine the effect of E. coli LPS on intestinal mucin secretion in weaning piglets. Methods: fifty-two piglets weaned at 21 days of age were fed a basal diet supplemented with four LPS levels (0.0, 0.3, 0.5, and 1.0 μg/mg) during 10 days. Piglets were slaughtered on days 1, 5, 7, and 10 post-weaning and samples of small and large intestine were taken for histochemical staining to determine goblet cell population and type of mucins produced (acidic, sulphated, non-sulphated, or neutral). Results: acidic mucin was reduced on day 5 post-weaning independently of the dietary LPS level supplied to piglets. Recovery of acidic mucins was observed during days 7 and 10 post-weaning. Neutral mucins increased on day 5 and decreased on days 7 and 10 post-weaning. High LPS levels decreased goblet cells population and secretion of all types of mucins. This effect was remarkably high for diet two (D2: 0.5 mg LPS/mg food). Conclusions: early weaning (21 d) and LPS addition to the diet affect mucin secretion and intestinal epithelium integrity by modifying goblet cell populations and their balance between acidic and neutral mucin secretion. These findings explain some abnormalities related with post-weaning diarrhea syndrome and help to explain its pathophysiology.